Competency-based Education Through Micro-credentials Offerings – A Pilot Study - Lim, Sok Mui; Puah, Shermain; Teo, Geok Bee; Or, Caleb; Chua, Eric Chern-Pin (Competency-Based Education Research Journal, 2025)
This pilot study examined the implementation of Competency-Based Education (CBE) through micro-credentials at the Singapore Institute of Technology (SIT), focusing on the perspectives of learners, instructors, and employers. Despite a growing global interest in CBE, empirical research on its effectiveness remains limited. SIT’s Competency-Based Stackable Micro-credential (CSM) program offers modular, industry-relevant learning for working adults, with micro-credentials functioning as standalone qualifications or stackable units toward a full degree. Findings from learner surveys indicated that the content was highly relevant to real-world jobs, and the learning could be applied to work. Instructors recognized the relevance of CBE to industry needs, despite the increased demands associated with content development, delivery, and learner support. Employers observed improvements in employee competencies and workplace engagement. The findings underscore the potential of CBE micro-credentials to offer flexible, industry-focused education pathways when supported by robust frameworks and comprehensive learner support services.